Tunable spacing dual wavelength Q-switched fiber laser based on tunable FBG device - M. Radzi, Nurnazifah; Abd Latif, Amirah; Ismail, Mohammad F.; Liew, Josephine Ying Chyi; Awang, Noor A.; Lee, Han K.; Ahmad, Fauzan; Norizan, Siti F.; Ahmad, Harith (MDPI, 2021)
A tunable spacing dual-wavelength Q-switched fiber laser is experimentally demonstrated based on a fiber Bragg grating tunable device incorporated in an erbium-doped fiber laser (EDFL). The system utilizes two identical fiber Bragg gratings (FBGs) at 1547.1 nm origin to enable two laser lines operation. The wavelength separations between two laser lines are controlled by fixing one of the FBGs while applying mechanical stretch and compression to the other one, using a fiber Bragg grating tunable device. The seven steps of wavelength spacing could be tuned from 0.3344 to 0.0469 nm spacing. Pulse characteristics for both close and wide spacing of dual-wavelength Q-switched fiber laser are successfully being recorded. The findings demonstrate the latest idea of dual-wavelength fiber laser based on FBG tunable device, which offers a wide range of future applications.